Hispanic-American Theater from Post-war: a sketch of approach (Olhares, 2015)
In the late nineteenth century, the Spanish-American drama had strong ties of dependency with the Spanish theater, however, from the early twentieth century, this relationship comes to change because of the key issues that emerged during the turn of century. Spain concluded the colonizing cycle of the Americas and emerging nations struggled to consolidate their political independence. The Latin American theater stated employing narrative procedures themselves, such as Maya and Quechua drama, comedy of manners and the grotesque “criollo”. In the postwar period, the assimilation of Expressionism, Symbolism and Epic Theater thematic-stylistic innovations, combined to the flow of European migrants in their clash with the indigenous tradition, laid the foundations of contemporary Hispanic-American theater.
Keywords: Latin-American theater; New playwrights of Mexico